Morphological and morphometric study of the opossum's dorsal root ganglia neurons - Soares, J. C. [UNESP]; Francia-Farje, L. A. D. [UNESP]; Horta-Junior, J. A. C. [UNESP]; Matheus, S. M. M. [UNESP] (Informa Healthcare, 2012)
The ultrastructural characteristics and the morphometric evaluation of the different types of neurons present in the dorsal root ganglia (DRG) of the South American opossum (Didelphis albiventris) were studied. Four adult male animals were used and the neurons from cervical and lumbar DRG were removed and processed for histological and transmission electron microscopy observations. The morphometric data were obtained from serial sections stained by H/E and Masson's trichrome. The number of neurons in cervical and lumbar DRG was 22 300 and 31 000, respectively. About 68% of the cervical neurons and 62.5% of the lumbar neurons presented areas up to 1300 mu m(2) and were considered as the small neurons of the DRG. The ultrastructural observations revealed two morphological types of neurons: clear large neurons and dark small neurons. The nuclei of both cell types are spherical and the chromatin is disperse and rarefected. The cytoplasm of the dark small neuron is more electron dense and shows a regular distribution of small mitochondria and many rough reticulum cisterns in the periphery. A small Golgi apparatus was close to the nucleus and many disperse neurofilaments occupy most parts of the cytoplasm. Smooth reticulum cisterns are rare and lipofucsin-like inclusions are present at some points. In the clear large neurons, the organelles are homogenously scattered through the cytoplasm. The neurofilaments are close packed forming bundles and small mitochondria and rough reticulum cisterns are disperse. Lipofucsin-like inclusions are more frequent in these cells.
Keywords: Primary sensitive neurons; ultrastructure; Didelphis albiventris; pseudounipolar neurons; spinal ganglion